Evaluating knowledge and self-rated competence of educational and speech-language professionals on language development and disorders - Elise de Bree; Madelon van den Boer (Stem-, Spraak- en Taalpathologie)
Purpose: Oral language abilities are essential for children's development and participation. Educational and healthcare professionals should know about language development and feel competent in delivering support to children with language problems or disorders. We evaluated the knowledge base, the self-rated competence and the reasons for this experienced competence in different groups of Dutch professionals, to gain insight in the qualities and needs in the educational support chain.